Ultrasound-guided platelet-rich plasma injection for traumatic painful neuroma of brachial plexus: a case report and literature review - Zhu, Haifeng; Deng, Zixuan; Xie, Yongqi; Qian, Guifeng; Wang, Danyu; Xie, Shaodong; Zhang, Yunyi; Yan, Peichun (Frontiers in Neurology, 2025)
Traumatic neuroma (TN) is a repair response of nerves to direct/indirect trauma or chronic inflammatory injury, commonly occurring after trauma or surgery. The authors report a rare case of a traumatic painful neuroma of the brachial plexus. Physical therapy and drug treatment failed to resolve the symptoms of allodynia and a palpable mass, which significantly reduced the patient’s quality. Ultrasound-guided injection of platelet-rich plasma (PRP) has shown significant efficacy in repairing the nerve and relieving pain. However, there is a lack of research on treating TN with PRP injection. This case demonstrates that ultrasound-guided injection of PRP can alleviate neuropathic pain caused by a traumatic painful neuroma of brachial plexus and improve the upper limb function.